2021
DOI: 10.1042/bsr20210817
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Curcuma longa extract and curcumin supplements on osteoarthritis: a systematic review and meta-analysis

Abstract: Objective: To assess the efficacy and safety of Curcuma longa Extract and curcumin supplements on osteoarthritis (OA). Methods: The databases such as Pubmed and Cochrane Library were searched to collect the article about Curcuma longa Extract and curcumin in the treatment of OA. Then, randomized controlled trials (RCTs) were selected and their data was extracted. Finally, the RevMan5.3 was utilized for risk of bias assessment and meta-analysis, the STATA15.0 were utilized for publication bias assessment, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 59 publications
(117 reference statements)
1
59
1
14
Order By: Relevance
“…Antcin B, H and K (antcins) are bioactive compounds isolated from Antrodia cinnamomea , a medical mushroom widely used in Asian countries [ 82 ]. Of note, Curcuma longa extract and curcumin supplements have shown comparable relieving effects on osteoarthritis to non-steroidal anti-inflammatory drugs (NSAIDs) with less adverse effects [ 83 ]. Likewise, EGCG , another widely accepted food supplement has shown various effects in combating metabolic syndrome and cancer [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antcin B, H and K (antcins) are bioactive compounds isolated from Antrodia cinnamomea , a medical mushroom widely used in Asian countries [ 82 ]. Of note, Curcuma longa extract and curcumin supplements have shown comparable relieving effects on osteoarthritis to non-steroidal anti-inflammatory drugs (NSAIDs) with less adverse effects [ 83 ]. Likewise, EGCG , another widely accepted food supplement has shown various effects in combating metabolic syndrome and cancer [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin has been extensively studied under experimental conditions as well as human clinical studies including treatment of osteoarthritis [23,[28][29][30][31], and bioavailability of curcuminoids plays an important role in the bioactivity such as exhibiting antioxidant and anti-inflammatory properties [32]. A recent study that used cell-based experimental models of osteoarthritis demonstrated that curcumin suppresses inflammation by blocking the NF-jB-Sox9 signaling pathway that plays a critical role in initiation of pathogenesis of osteoarthritis [29].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that the use of CUR as a dietary supplement was better than glucosamine (GA) and chondroitin in improving OA in the knee joints, hip joints, and hands in the short term (Liu et al, 2018b). Other studies have also shown that CUR can reduce OA pain and improve joint function while reducing the risk of adverse events (Panahi et al, 2014;Bannuru et al, 2018;Zeng et al, 2021) and can serve to decrease the use of NSAIDs which has more adverse effects (Grover and Samson, 2016;Wang et al, 2021a). At present, there are many methods, such as nanoparticles, liposomes, micelles, and phospholipid complexes, which can extend drug release time and increase permeability and resistance to clearance (Anand et al, 2007;Wang et al, 2019).…”
Section: Curcuminmentioning
confidence: 99%